A hydrazone-based turn-on fluorescent probe for peroxynitrite detection and live-cell imaging. (December 2019) - Kim, Sudeok; Ko, Chang Woo; Lim, Taeho; Yoo, Soyeon; Ham, Hye Jin; Kang, Seo-Young; Kang, Seungyoon; Cho, Steve K.; Han, Min Su
Abstract: Peroxynitrite (ONOO − ) plays an important physiological role and is related to various clinical diseases. In the past two decades, a number of fluorescent probes have been developed to detect ONOO −, however, most of them show insufficient selectivity over other reactive oxygen species (ROS) and reactive nitrogen species (RNS), long response time, low fluorescence enhancement in the presence of ONOO −, and poor water solubility. Herein, a hydrazone-based fluorescent probe that overcomes the abovementioned problems was designed and synthesized by a single-step reaction. This probe exhibits high sensitivity to ONOO −, with ~76-fold enhancement of fluorescence intensity within 1 min, and excellent selectivity for ONOO − over various ROS/RNS. Furthermore, this probe was successfully applied for the visualization of ONOO − in RAW264.7 and H1299 cells. Graphical abstract: Image 1 Highlights: A hydrazone-based turn-on fluorescent probe for peroxynitrite (ONOO − ) was developed. This probe exhibits high sensitivity, excellent selectivity, and a rapid response time. This probe was successfully applied to the imaging of exogenous ONOO − in living cells.